2008
DOI: 10.1111/j.1365-313x.2008.03441.x
|View full text |Cite
|
Sign up to set email alerts
|

The tryptophan pathway is involved in the defense responses of rice against pathogenic infection via serotonin production

Abstract: SummaryThe upregulation of the tryptophan (Trp) pathway in rice leaves infected by Bipolaris oryzae was indicated by: (i) enhanced enzyme activity of anthranilate synthase (AS), which regulates metabolic flux in the Trp pathway; (ii) elevated levels of the AS (OASA2, OASB1, and OASB2) transcripts; and (iii) increases in the contents of anthranilate, indole, and Trp. The measurement of the contents of Trp-derived metabolites by highperformance liquid chromatography coupled with tandem mass spectrometry revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
232
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(240 citation statements)
references
References 67 publications
8
232
0
Order By: Relevance
“…And lesion formation, wounding, and pathogen infection also activate tryptophan-dependent IAA biosynthesis pathways (Normanly and Bartel, 1999;Zhao and Last, 1996). Furthermore, the tryptophan biosynthesis pathway is also involved in the defense responses (Ishihara et al, 2008). Thus, we can postulate that ATAF2 might regulate auxin biosynthesis pathway and this regulation could be connected with ATAF2-mediated plant defense system.…”
Section: Discussionmentioning
confidence: 97%
“…And lesion formation, wounding, and pathogen infection also activate tryptophan-dependent IAA biosynthesis pathways (Normanly and Bartel, 1999;Zhao and Last, 1996). Furthermore, the tryptophan biosynthesis pathway is also involved in the defense responses (Ishihara et al, 2008). Thus, we can postulate that ATAF2 might regulate auxin biosynthesis pathway and this regulation could be connected with ATAF2-mediated plant defense system.…”
Section: Discussionmentioning
confidence: 97%
“…Bipolaris oryzae (MAFF 305067) was provided by the NIAS Genebank (http://www.gene.affrc.go.jp/index_en.php). B. oryzae inoculation was performed as previously described by Ishihara et al (2008). 11) 3.…”
Section: Plant Materials and Pathogenmentioning
confidence: 99%
“…B. oryzae inoculation was performed as previously described by Ishihara et al (2008). 11) 3. Chemicals JA was prepared by alkaline hydrolysis of methyl jasmonate (Tokyo Chemical Industry, Tokyo, Japan).…”
Section: Plant Materials and Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 A surge in the activity of anthranilate synthase ( EC : 4.1.3.27) and accumulation of tryptophan-derived metabolites (including serotonin) has been observed in the leaves of rice plants in response to biotic stress. 78 Recent reports based on gene annotation and analysis of metabolic pathway network database (RiceCyc) in rice have further shown that TDC1 and TDC3 are induced by abiotic and biotic stress factors. 9 Melatonin biosynthesis and its regulation involve the activity of enzymes downstream to serotonin biosynthesis, namely serotonin N-acetyltransferase (SNAT, E.C.…”
mentioning
confidence: 99%